The Effect of Total Asset Turnover, Debt-to-Equity Ratio, and Net Profit Margin on Stock Returns: Empirical Evidence from FMCG’s Sub-Sector Companies Listed on the Indonesia Stock Exchange (2023–2025) - Haryanti Juniarsih; Djolin Henriansah (Journal of Managerial Sciences and Studies, 2026)
This study empirically investigates the influence of Total Asset Turnover (TATO), Debt-to-Equity Ratio (DER), and Net Profit Margin (NPM) on stock returns among retail sub-sector companies listed on the Indonesia Stock Exchange (IDX) over the 2023–2025 period. Anchored in Signaling Theory, this study posits that financial ratios function as informational signals that shape investor perception and, consequently, equity valuation in the capital market. The retail sector was selected as the research locus given its acute sensitivity to macroeconomic fluctuations and the structural challenges posed by the post-COVID-19 recovery environment. This study adopts a quantitative causal research design using secondary data obtained from annual financial statements and official stock price records. A purposive sampling technique yielded a final sample of 20 companies, generating 80 panel observations. Data were analyzed using panel data regression with the Common Effect Model (CEM) selected as the most appropriate estimator based on the Chow Test and Lagrange Multiplier Test. To address detected heteroscedasticity, the Panel Estimated Generalized Least Squares (EGLS) with cross-section weights was applied. The findings reveal that TATO and NPM each exert a positive and statistically significant effect on stock returns, whereas DER demonstrates no significant influence. Simultaneously, all three variables jointly explain 31.47% of the variation in stock returns, with the remaining variance attributable to external macroeconomic and firm-specific factors beyond the model's scope. These results corroborate the signaling framework by confirming that asset utilization efficiency and net profitability constitute the principal fundamental signals prioritized by market participants in the retail industry. The findings carry practical implications for both investors — who are advised to emphasize operational efficiency and profitability metrics in their stock selection process — and for corporate management, which should treat asset optimization and margin improvement as strategic levers for enhancing market valuation.